The Value of Ultrasound Screening for Proximal Vein Thrombosis after Total Hip Arthroplasty - Verlato, Fabio; Bruchi, Olinto; Prandoni, Paolo; Camporese, Giuseppe; Maso, Gianni; Busonera, Flavio; Girolami, Antonio; Andreozzi, Giuseppe Maria; for the W. O. D. O. S. Investigators Group (Thrombosis and Haemostasis, 2001)
The role of ultrasound screening for proximal deep-vein thrombosis (DVT) following major hip surgery is controversial. 202 consecutive patients, who had received warfarin prophylaxis after total hip arthroplasty underwent a bilateral ultrasound assessment of the proximal vein system (using the criterion of vein compressibility) before hospital discharge. In the 9 patients (4.5%; 95% CI, 2.1-8.3%) with positive test anticoagulant treatment was successfully continued for three months. In all the remaining 193 patients the warfarin treatment was withdrawn. A second ultrasound test was performed 15 days later, and showed a new (asymptomatic) abnormality compatible with proximal DVT in 2 patients (1.0%; 95% CI, 0.1-3.7%). All other 191 patients remained asymptomatic until the completion of a 3-month follow-up period (rate of symptomatic thromboembolism, 0/191, 0%; 95% CI, 0-1.9%).Because of the relatively high incidence of proximal DVT in patients undergoing major orthopaedic surgery under warfarin prophylaxis, screening for proximal DVT at hospital discharge in these patients is indicated. The negativity of this test has the potential of safely preventing the extension of anticoagulation beyond hospital stay. A larger controlled study in which the value of this strategy is tested against the prolongation of oral anticoagulation in patients with a negative ultrasound screening at discharge is indicated.
Keywords: Ultrasound; deep vein thrombosis; hip arthroplasty; oral anticoagulants